Musculoskeletal Consequences of Systemic Corticosteroid Misuse in a Patient with Psoriasis - Uddin, Mohammad Moin; Khan, Aminuddin A; Sultana, Nusrat; Taslim, Abu (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
This is a case history of a patient with psoriasis with indiscriminate systemic corticosteroid use for a prolonged period. A single patient can be victim of multiple deleterious effects of corticosteroids. The aim of this case discussion is not only to describe the myriads of sequels of corticosteroid misuse effecting musculoskeletal system severely but simultaneously to rethink about prescription of steroid in psoriasis, too. Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 80-82